2015
DOI: 10.7554/elife.06935
|View full text |Cite
|
Sign up to set email alerts
|

A high affinity RIM-binding protein/Aplip1 interaction prevents the formation of ectopic axonal active zones

Abstract: Synaptic vesicles (SVs) fuse at active zones (AZs) covered by a protein scaffold, at Drosophila synapses comprised of ELKS family member Bruchpilot (BRP) and RIM-binding protein (RBP). We here demonstrate axonal co-transport of BRP and RBP using intravital live imaging, with both proteins co-accumulating in axonal aggregates of several transport mutants. RBP, via its C-terminal Src-homology 3 (SH3) domains, binds Aplip1/JIP1, a transport adaptor involved in kinesin-dependent SV transport. We show in atomic det… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
31
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 97 publications
6
31
0
Order By: Relevance
“…This study found that BRP and RIM-binding protein (RBP) can be co-transported[62]. Intriguingly, RBP and BRP transport could be uncoupled[62]. Indeed, our data supports such an idea and suggests the possibility that BRP could be transported via a distinct mechanism.…”
Section: Discussionsupporting
confidence: 69%
“…This study found that BRP and RIM-binding protein (RBP) can be co-transported[62]. Intriguingly, RBP and BRP transport could be uncoupled[62]. Indeed, our data supports such an idea and suggests the possibility that BRP could be transported via a distinct mechanism.…”
Section: Discussionsupporting
confidence: 69%
“…Because active kinesin-dependent protein transport is required for long-term homeostatic plasticity in gluRIIA Null mutants 27 , we asked whether BRP/RBP transport mechanisms might be employed for AZ remodeling. For this we investigated proteins involved in BRP/RBP transport by their mutation which causes abnormal BRP/RBP accumulation in the moto-neuronal axons, such as Atg1 (Unc-51) 28 , serine–arginine (SR) protein kinase at location 79D (Srpk79D; 29, 30 ), and App-like interacting protein (Aplip-1, Jip1 or JNK interacting protein in mammals), a selective RBP transport-adaptor 31 (Fig. 3a,b).…”
Section: Resultsmentioning
confidence: 99%
“…The backbone rmsd is 0. 53 A when they are overlaid using the backbone heavy atoms in folded regions (residues 559-609 of SNK1-SH3, residues 530-582 of SNK2-SH3, and residues 476-527 of SNK3-SH3) (Fig. 2B).…”
Section: Resultsmentioning
confidence: 99%